2013
DOI: 10.1038/cddis.2013.132
|View full text |Cite
|
Sign up to set email alerts
|

Glucose 6-phosphate dehydrogenase deficiency enhances germ cell apoptosis and causes defective embryogenesis in Caenorhabditis elegans

Abstract: Glucose 6-phosphate dehydrogenase (G6PD) deficiency, known as favism, is classically manifested by hemolytic anemia in human. More recently, it has been shown that mild G6PD deficiency moderately affects cardiac function, whereas severe G6PD deficiency leads to embryonic lethality in mice. How G6PD deficiency affects organisms has not been fully elucidated due to the lack of a suitable animal model. In this study, G6PD-deficient Caenorhabditis elegans was established by RNA interference (RNAi) knockdown to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…7 The morphology of G6PD-deficient embryos was examined by microscopy (Figure 1). Unlike normal embryos, G6PD-deficient embryos displayed irregular, flattened and an egg-filling phenotype, indicating that the structure of G6PD-deficient embryos may be influenced by osmotic changes (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The morphology of G6PD-deficient embryos was examined by microscopy (Figure 1). Unlike normal embryos, G6PD-deficient embryos displayed irregular, flattened and an egg-filling phenotype, indicating that the structure of G6PD-deficient embryos may be influenced by osmotic changes (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…7 Reduced NADPH production and enhanced lipid peroxidation are associated with increased iPLA activity in G6PD-deficient embryos. Inhibition of multiple iPLAs by genetic manipulation can alleviate the embryonic impairment caused by G6PD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence from animal research supporting the hypothesis that specific helminth infections protect against metabolic disease. Mouse studies have shown that experimental infection with helminths can result in reduced fasting glucose concentrations, decreased fasting insulin concentrations, improved glucose and insulin tolerance, and less insulin resistance in comparison to non-infected controls [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical and clinical studies have shown that reducing glucose intake was associated with negative effect on tumor growth [ 107 111 ]. Moreover, it has been show that in a tumor in xenograft mouse model, the tumor growth of p53n −/− cells was reduced in mice fed with a diet containing no serine and glycine [ 52 ].…”
Section: Discussionmentioning
confidence: 99%